Analysis of the chemical composition of root essential oil from Indian sarsaparilla (Hemidesmus indicus) and its application as an ecofriendly insecticide and pharmacological agent - Arunaksharan Narayanankutty (Elsevier, 2021)
The Indian sarsaparilla (Hemidesmus indicus) is a commonly used plant in Indian traditional medicine of Ayurveda for the preparation of various non-alcoholic beverages. However, limited studies are available on the essential oil of H. indicus roots (HRO); therefore, the study evaluated the antioxidant, anti-inflammatory and antidiabetic activities of H. indicus root essential oil as well as insecticide potential against the common pests of stored food materials (Sitophilus oryzae, Callosobruchus maculatus and Tribolium castaneum). The repellant efficacy of HRO was found to be high against S. oryzae (8.21 ± 0.55 μg/mL). Likewise, the fumigant potential was also observed for HRO against these pests; the higher activities were observed against S. oryzae and C. maculatus (32.46 ± 1.42 and 35.18 ± 1.62 μg/L). Besides, the essential oil was also found to be active as a contact poison, however, against all the three pests, the toxicity was above 100 μg/mm3, being the highest against C. maculatus (122.8 ± 3.57 μg/mm3). To analyze the possible effect of the essential oil on grains, the different grains were allowed to germinate and compared to that of normal; thus, the non-toxic nature of HRO against the stored products is also confirmed. The essential oil shown to have DPPH hydrogen peroxide and ABTS radical scavenging, nitric oxide scavenging potential, and inhibition of lipoxgenase, alpha-amylase and alpha-glucosidase. Overall, the present study concludes that the H. indicus may be a suitable repellant and fumigant agent against different pests of stored products and a possible antioxidant, anti-inflammatory, and anti-diabetic agent.